جودة حياة العمل لدى أعوان الحماية المدنية - العبدي,فاطمة الزهراء (University of Eloued جامعة الوادي, 2024)
تهدف الدراسة الحالية للكشف عن مستوى جودة حياة العمل لدى أعوان الحماية المدنية، تكونت عينة الدراسة من (295) عون تدخل، بنسبة (100%) ذكور، حيث بلغ متوسط السن لديهم (35.83) سنة وبانحراف معياري قدر بـ (07.45)، تم اختيارهم بطريقة مقصودة، ولتحقيق أهداف البحث اتبعنا المنهج الوصفي، ولتحقيق أهداف الدراسة استخدمت الباحثة مقياس العوامل الحاكمة لجودة حياة العمل المعد من قبل المغربي (2004)، وبعد جمع البيانات وتفريغها ومعالجتها توصلت النتائج إلى أنّ المستوى الغالب هو مستوى جودة حياة العمل المرتفع لدى أعوان الحماية المدنية.Abstract: The aim of this present study is to reveal the level of quality of work life of civil protection agents. The sample consisted of (295) interventionists, a percentage of (100%) males, where their average age (35.83) years and with a standard deviation of about (07.45) years, were chosen in a deliberate manner. To achieve the research objectives we adopted the descriptive method. To achieve the aim of this study the researcher used the factors governing the quality of work life scale. After collecting, unloading and processing the data, the results were as follows: The prevailing standard is the high quality of work life of civil protection agents.
Keywords: Quality of Work Life; Shift Work; Civil Protection Agents